Mapping global trends in research of stem cell therapy for COVID-19: A bibliometric analysis - Zhang, Xinkang; Cai, Jiehui; Chen, Lingzhi; Yang, Qiuping; Tian, Huiting; Wu, Jinyao; Ji, Zeqi; Zheng, Daitian; Li, Zhiyang; Chen, Yexi (Frontiers in Public Health, 2022)
Over the past two years, the world has witnessed the devastating effects of the COVID-19 pandemic on humanity. Fortunately, stem cell therapy is widely used in clinical practice for the treatment of COVID-19 and has saved the lives of many critically ill patients. A bibliometric analysis of this field can analyze research hotspots and predict the research trends. This research analyzed documents from Web of Science between the years 2020-2022. The bibliometrics software bibliometrix, VOSviewer, and CiteSpace were used to complete the visual analysis of publications, authors, countries, documents, organizations, collaborative networks, and keywords clustering. 896 publications on COVID-19 stem cell therapy were included in the analysis, including 451 articles and 445 review articles. The field grew at the average growth rate of 103.17% between 2020 and 2021. The United States had the highest number of publications and citations. Many developing countries had also contributed significantly to the field. The journal with the most articles was Stem Cell Research & Therapy. The most cited journal was Stem Cell Reviews and Reports. The published documents were focused on five themes: “Cell Biology”, “Medicine Research Experimental”, “Cell Tissue Engineering”, “Immunology”, and “Pharmacology Pharmacy”. The bibliometric analysis revealed that current clinical trials had validated stem cell therapy's remarkable potential in treating COVID-19 and its complications. It is foreseeable that future research in this area will continue to increase. With the help of bibliometric analysis, researchers can identify the current state of research and potential research hotspots.